2013
DOI: 10.1080/03601234.2013.775000
|View full text |Cite
|
Sign up to set email alerts
|

Acute toxicity and environmental risk of teflubenzuron toDaphnia magna,Poecilia reticulataandLemna minorin the absence and presence of sediment

Abstract: This study aimed to estimate the acute toxicity of teflubenzuron (1-(3,5-dichloro-2,4-difluorophenyl)-3-(2,6-difluorobenzoyl)urea) (TFB) for Daphnia magna, Lemna minor and Poecilia reticulata, in the absence and presence of sediment; evaluate the effect of sediment on the TFB bioavailability; and to classify this insecticide according to its environmental poisoning risk for agricultural and aquaculture uses. The tests of TFB acute toxicity were conducted in static system in a completely randomized design with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 16 publications
0
5
1
Order By: Relevance
“…It should be noted that in the present study, the estimated LC50 for the effect of TEF on D. magna survival in the ≤24-hpr group was 16.8 μg/L, which was 60 times higher than previously reported (Medeiros et al, 2013). This large discrepancy might arise from the use of a commercial formulation of TEF by Medeiros and coworkers.…”
Section: Resultscontrasting
confidence: 83%
“…It should be noted that in the present study, the estimated LC50 for the effect of TEF on D. magna survival in the ≤24-hpr group was 16.8 μg/L, which was 60 times higher than previously reported (Medeiros et al, 2013). This large discrepancy might arise from the use of a commercial formulation of TEF by Medeiros and coworkers.…”
Section: Resultscontrasting
confidence: 83%
“…For instance, the 96 h-EC 50 values of thiamethoxam to Navicula pelliculosa, Raphidocelis subcapitata , Lemna gibba , and Anabaena flos-aquae were greater than 90 mg/L . The 7 d-EC 50 of teflubenzuron to Lemna minor even exceeded 1100 mg/L . However, several researches showed that phenylpyrazole pesticides were highly toxic to freshwater algae.…”
Section: Resultsmentioning
confidence: 99%
“…42 The 7 d-EC 50 of teflubenzuron to Lemna minor even exceeded 1100 mg/L. 43 However, several researches showed that phenylpyrazole pesticides were highly toxic to freshwater algae. The 72 h-EC 50 of rac-fipronil to Scenedesmus obliquus was 0.54 mg/L, and R-fipronil was found to be approximately 5 times as toxic as S-fipronil with 72 h-EC 50 values of 0.29 and 1.50 mg/L.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Few data are available on dose descriptors for flubenzurons, particularly on non‐targeted marine crustaceans and after oral administration of the pesticide. For the cladocera Daphnia magna , teflubenzuron (48 hours EC 50 : 0.26 μg/L) was 27.3 times more toxic than diflubenzuron (48 hours EC 50 : 7.1 μg/L) when exposed to the pesticide dissolved in water (Medeiros et al, ). A no‐observed‐effect concentration of 0.062 μg/L was found for D. magna after 21 days of waterborne exposure (Scheepmaker, ).…”
Section: Introductionmentioning
confidence: 99%